Predicting Patient No-Shows in an Academic Pediatric Neurology Clinic. (June 2022) - Peng, Jin; Patel, Anup D.; Burch, Maggie; Rossiter, Samantha; Parker, William; Rust, Steve
Background: No-shows can negatively affect patient care. Efforts to predict high-risk patients are needed. Previously, our epilepsy clinic identified patients with 2 or more no-shows or late cancelations in the past 18 months as being at high risk for no-shows. Our objective was to develop a model to accurately predict the risk of no-shows among patients with epilepsy seen at our neurology clinic.Methods: Using electronic health record data, we developed a least absolute shrinkage and selection operator (LASSO)–regularized logistic regression model to predict no-shows and compared its performance with our neurology clinic's above-mentioned ad hoc rule.Results: The ad hoc rule identified 13% of patients seen at our neurology clinic as high-risk patients for no-shows and resulted in a positive predictive value of 38%. In comparison, our LASSO model resulted in a positive predictive value of 48%. Our LASSO model identified that lack of private insurance, inactive Epic MyChart, greater past no-show rates, fewer appointment changes before the appointment date, and follow-up appointments were more likely to result in no-shows.Conclusions: Our LASSO model outperformed the ad hoc rule used by our neurology clinic in predicting patients at high risk for no-shows. Social workers can use the no-show risk scores generated by our LASSO model to prioritize high-risk patients for targeted intervention to reduce no-shows at our neurology clinic.